KONDISI PERIKANAN TANGKAP DI KABUPATEN KEPULAUAN ARU - Ririhena, John Etry (LPPM Universitas Hein Namotemo, 2017)
This study aims to determine the condition of fisheries in the district of Aru Islands. The benefits of this research provide benefits to the government of the Aru Islands in managing existing marine resources and advises the government Aru Islands in this case the Department of Fisheries and Marine can better control again in giving permission or fishing activities. The study was conducted in May 2013. The study shows non-fish fishing and highest in 2011 74.357 tons, while the lowest was in 2007 with a catch of 36.210 tonnes, the number of fishermen and fishing groups were highest in 2011 with the number of the 17.982 fishermen and fishing groups 2943, while the lowest was in 2007 with the number of fishermen 10.883 people and fishermen groups 1.282, the number of fishing gear is the highest in 2011 with the number of 25.249 units, while the lowest was in 2010 and 2009 with the number of 19.109 units, the number of boat / motor boat highs in 2011 with the number of boat / motorboat 4.417, while the lowest was in 2008 with the number 2.849. Recaps fishery business license (License) in 2011 and 2012 noted that the letter of the new or extended in 2012 more than 2011, because in 2012 the activity of arrest or other more than in 2011. In 2013 SIPI more than SIKPI , For the new 59-renew only 17 while limiting the number of SIPI letter amounted to 76. For new SIKPI no extended while only five letters.